KETERKAITAN ANTARA MODAL SOSIAL DENGAN EFISIENSI KELEMBAGAAN PADA KOPERASI PONDOK PESANTREN SIDOGIRI, PASURUAN - FARAHDILLA KUTSIYAH; AGOES KAMAROELLAH; UMMU KALSUM (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2019)
Sidogiri Islamic Boarding School is one of the oldest Islamic boarding schools and is capable of being independent in its operational activities by having very rich resources and this institution is also an example of success in developing Islamic economics. The deﬁnition of